2006
DOI: 10.1002/jssc.200500499
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse porous poly(vinyl acetate-co-divinylbenzene) particles by single-stage seeded polymerization: A packing material for reversed phase HPLC

Abstract: A single-stage swelling and polymerization method was proposed for the synthesis of monodisperse porous poly(vinyl acetate-co-divinylbenzene) [poly(VAc-co-DVB)] particles with different VAc/DVB feed ratios. The particles obtained with the VAc/DVB feed ratio of 50:50 v/v had a narrow pore size distribution exhibiting a sharp peak at 30 nm. Based on this distribution the mean pore size and the specific volume were determined as 12 nm and 1.39 mL/g, respectively. The specific surface area of poly(VAc-co-DVB) part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…The slopes between 0.10 and 0.19 were obtained with different ACN concentrations, and the slope increased with increasing ACN concentration. The results are in accordance with the methylene selectivity range of silica-based and polymer-based reversedphase columns [31][32][33]. The results indicated that separation power of poly(GDMA-co-GDGDA) column increased with decreasing ACN concentration in the mobile phase.…”
Section: Chromatographysupporting
confidence: 78%
“…The slopes between 0.10 and 0.19 were obtained with different ACN concentrations, and the slope increased with increasing ACN concentration. The results are in accordance with the methylene selectivity range of silica-based and polymer-based reversedphase columns [31][32][33]. The results indicated that separation power of poly(GDMA-co-GDGDA) column increased with decreasing ACN concentration in the mobile phase.…”
Section: Chromatographysupporting
confidence: 78%
“…A single‐step swelling method optimized from the method proposed by Caglayan29 was chosen for preparation of poly(DVB), poly(VAc‐ co ‐DVB), poly(EDMA), and poly(GMA‐ co‐EDMA) particles. In general, a homogeneous organic phase was obtained by admixing the monomer mixture with toluene‐containing BPO initiator (Tables 2 and 3).…”
Section: Methodsmentioning
confidence: 99%
“…Since emulsion prepared seeds are generally in the submicron range, they are suitable for obtaining particles up to 10 µm in diameter after the suspension polymerization stage [68][69]. On the other hand, dispersion polymerized seeds can be in the range of 1-20 µm, thus 10-200 µm particles can be obtained in the suspension polymerization stage [70][71][72][73][74][75][76][77][78][79]. Note that a volume enlargement of 10 6 times would be needed for a 1 µm seed to be swollen by the new monomer(s) to 100 µm.…”
Section: Seeded Suspension Polymerizationmentioning
confidence: 99%